Position of Experts of the Union of Pediatricians of Russia Regarding the Worsening Global Situation with Poliomyelitis Virus - L. S. Namazova-Baranova; A. A. Baranov; N. I. Briko; O. E. Ivanova; R. V. Polibin; A. Y. Rtischev; V. F. Uchaikin; M. V. Fedoseeko; I. V. Feldblium; V. P. Chulanov; A. K. Shakaryan; O. V. Shamsheva (Эпидемиология и вакцинопрофилактика, 2023)
.